PEMBELAJARAN AGAMA BERBASIS DIGITAL - Adi Mukhtar (Journal of Community Devation, 2025)
In the current era of globalization, consciously or unconsciously, the influence of technology-based media is very large. Progressively, with the exchange of large amounts of information, the media has influenced all aspects of our lives, although to different degrees. The development of the world of computers has reached very impressive developments. It has been proven that practically all work in the world has been controlled by computers. Just like other fields, computers are also closely related to education. In the field of teaching, computers make it possible to carry out distance learning, or learning without facing each other. However, the problems that arise with glue are not as easy as imagined. For example, in this case, teachers who master the subject matter, most of them are not yet able to present forms of learning on the computer, while computer experts who are able to understand everything on the computer, usually do not master the subject matter. We need software that can help teachers express their ideas into the computer. A multimedia-based teaching method that can help teachers convey lesson material according to the context. Control via computer is required, therefore independent learning or distance learning can be done.